Pattern of Drug Abuse in Kashmir and the Role of Forensics: An Immediate Need to Act and Introspect (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
Illicit manufacture, trafficking and abuse of drugs constitute one of the most significant potent drug problems worldwide having detrimental effects on the users as well as on the society. Addicts consume the substances in such amounts that are neither approved nor advised by the medical professionals. The death-related incidents due to the misuse of the substances have not only created havoc in criminality but are a cause for huge health-related issues. The present study was therefore aimed to address the pattern of drug abuse in the state of Jammu and Kashmir with special idea of forensics which in a decisive way may help the investigators to pursue legal action against individual(s) suspected of drug-related crimes. Forensic analysis of drugs may help in a way where the challenging goal is to determine the identity of the illegal drug for its constituents. It is only by virtue of the results of the analysis that make law enforcement agencies pursue criminal charges against the offenders and accordingly the court to determine appropriate sentencing where the life or liberty of a person is at a stake.
Keywords: Drug abuse; Crime; Forensic; Trafficking; Social disintegration; Law enforcement; Identification